The photographic pact of belief: alibi, testimony, and the contemporary reconfiguration of visual evidence - Libardi, Virgilio (Farol, 2026)
This text examines, from a sociological perspective, the historical credibility of photography as a form of visual testimony in light of contemporary concerns regarding synthetic images produced by artificial intelligence. Through a theoretical-conceptual reflection, it is argued that this credibility stemmed from social and institutional processes that stabilized a photographic pact of belief. Consequently, the notions of "photographic alibi" and "photographic pact of belief" are proposed to understand the contemporary reconfiguration of visual evidence. The conclusion suggests that the current issue may have less to do with the disappearance of trust in images than with the emergence of new regimes of visual credibility. Keywords: photography; sociology of the image; visual culture; artificial intelligence; visual trust